Particle Confinement in Penning Traps An Introduction - Vogel, Manuel (Springer Series on Atomic, Optical, and Plasma Physics,, 2018)
This book provides an introduction to the field of Penning traps and related experimental techniques. It serves both as a primer for those entering the field, and as a quick reference for those working in it. The book is motivated by the observation that often a vast number of different resources have to be explored to gain a good overview of Penning trap principles. This is especially true for students who experience additional difficulty due to the different styles of presentation and notation. This volume provides a broad introductory overview in unified notation.